Factors affecting the participation of Caribbean countries in the Free Trade Area of the Americas (ECLAC Port of SpainTT, 1995)
Examines some of the measures used by various trade and integration groupings to deal with the question of unequal gains among member countries. Discusses the potential costs and benefits of participation by the small economies in the FTAA. Suggests some policy actions which might assist the smaller countries to adjust to the widening hemispheric market.
Bibliography: p. 20. Additional copy located in the Office of the Secretary-General